THE VILLAGE-OWNED ENTERPRISE “KITA” STRATEGY TO ACCELERATE THE IMPLEMENTATION OF FINANCIAL MANAGEMENT PRINCIPLES - Aprina Nugrahesthy Sulistya Hapsari; Intiyas Utami; Yohanes Yakobus Werang Kean (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2022)
BUMDes is one of the government's goals in restoring the Indonesian economy, as stated in the Village SDGs. However, the findings show that there are still many BUMDes that cannot answer the government's expectations and instead commit fraud in the management of BUMDes funds. This study aims to see from the point of view of the implementation of principles in the financial management of BUMDes, what is the strategy of BUMDes in realizing harmony with the Village SDGs, especially in the goal of recovering the Indonesian economy? The main object of this research is BUMDes "KITA" Central Wologai, Detusoko District, Ende Regency, East Nusa Tenggara. The research method is descriptive qualitative using primary data obtained through semi-structured interviews. The results show that the BUMDes "KITA" Wologai Tengah has attempted to implement the principles of BUMDes financial management at every stage to "satisfy" the needs of stakeholders even though there are still obstacles in it. The obstacles are, among others, the adjustment period that is currently being carried out by BUMDes managers to be more adaptive to the applicable rules regarding BUMDes financial management. Another problem is related to human resources who have a minimum educational background and do not understand generally accepted accounting principles and the sophistication of information technology as a supporter of BUMDes financial management. The theoretical implications, related to the current laws and regulations, are still limited to the principles of village financial management, so a reference is needed to assess the financial management performance of BUMDes. Practically, this research provides the results of applying the principles of financial management to newly established BUMDes, so that many things can be input for BUMDes "KITA” as well as providing suggestions for further research that can be re-examined after this BUMDes in the developing stage.